Make Believe in Film and Fiction - Kroeber, K. author. aut Link
IX, 228 p.
Keywords: This study provides the first detailed contrast between the experiences of reading a novel and watching a movie. Kroeber shows how fiction evokes morally inflected imagining, and how movies reveal through magnification of human movements and expression subjective effects of complex social changes.